EFFECTS OF LOW CARBOHYDRATE DIETS IN INDIVIDUALS WITH TYPE 2 DIABETES MELITUS : THE SYSTEMATIC REVIEW - Talilah, Stephanie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
People who have type 2 diabetes have been known to use low carbohydrate dietary (LCDs) approaches for some time now, but the standard of care in many parts of the world has been centered on the utilization of a low fat, calorie controlled diet — in line with that which is typically recommended for the general population — for the better part of the last few decades. This has been the case even though it has been known for some time now that people who have type 2 diabetes use low carbohydrate dietary (LC Patients who have been diagnosed with diabetes are often given the recommendation to participate in some kind of food intervention program; however, several authoritative organizations have varying recommendations in this area. Before insulin was discovered, the most common method for managing diabetes was via the use of restricted diets that focused on limiting carbohydrate intake. However, in recent years, there has been a shift away from favoring these diets as an effective technique for managing diabetes. Because insulin resistance is a key underlying mechanism of type 2 diabetes, which is driven in part by chronic hyperglycemia, it has been suggested that lowering dietary intake of carbohydrates, the majority of which is absorbed as glucose or fructose, will improve blood glucose control and outcomes of type 2 diabetes. This is because chronic hyperglycemia is one of the factors that contributes to the development of insulin resistance. This article demonstrates that LCD may reliably reduce HbA1c levels; however, the reduction in HbA1c that takes place once a patient has a HbA1c level of less than 8 is not considered to be meaningful.